1997
DOI: 10.1038/sj.leu.2400609
|View full text |Cite
|
Sign up to set email alerts
|

Predominance and characteristics of Burkitt lymphoma among children with non-Hodgkin lymphoma in northeastern Brazil

Abstract: The purpose of this paper was to define the histologic distrito the endemic (African) and sporadic forms of Burkitt lymbution, clinical features, and treatment response of childhood phoma, which differ in their clinical presentation, regional non-Hodgkin lymphoma (NHL) in northeastern Brazil. We incidence, association with Epstein-Barr virus, and biologic Patients and methodsThere was a striking predominance of the small noncleaved cell (Burkitt) subtype, which occurred in 92 of the 98 children and adolescent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
27
1
3

Year Published

2001
2001
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 3 publications
7
27
1
3
Order By: Relevance
“…The present study describes the epidemiological and clinical characteristics of 142 Egyptian pediatric NHL patients admitted to two Pediatric Oncology Units. Patients aged <10 years consituted >88.5% of our study sample and there was a trend toward a decrease of the relative incidence with increasing age, with 88.5 and 11.5% for the age groups of 0-10 and >10 years, respectively, which was consistent with previously reported findings (16)(17)(18). Sandlund et al (1) and Manipadam et al (19) reported that the incidence of NHL increases uniformly with age and is rarely diagnosed before 2 years of age.…”
Section: Discussionsupporting
confidence: 82%
“…The present study describes the epidemiological and clinical characteristics of 142 Egyptian pediatric NHL patients admitted to two Pediatric Oncology Units. Patients aged <10 years consituted >88.5% of our study sample and there was a trend toward a decrease of the relative incidence with increasing age, with 88.5 and 11.5% for the age groups of 0-10 and >10 years, respectively, which was consistent with previously reported findings (16)(17)(18). Sandlund et al (1) and Manipadam et al (19) reported that the incidence of NHL increases uniformly with age and is rarely diagnosed before 2 years of age.…”
Section: Discussionsupporting
confidence: 82%
“…We found evidence of a high prevalence of NHL of the Burkitt histological subtype (78.2%), when compared with American and European data. 3 Sandlund et al 6 have previously made the same observation with relation to the distribution of histological types, reporting a frequency of 94% of Burkitt's lymphoma in children with NHL in our region.…”
Section: Discussionsupporting
confidence: 55%
“…3 In our study we observed that NHL affects younger children than those described in foreign literature and this fact is compatible with other reports that have described other Brazilian experiences. 6,7,15,16 The possibility of infectious etiology, principally related to the Epstein-Barr virus, 4 being involved in the pathogenesis of Burkitt lymphomas may be a partial explanation for the emergence of this disease in younger patients in our region, since it is believed that populations in less privileged socioeconomic situations are exposed to infectious agents earlier.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Association of EBV infection with Burkitt's lymphoma and Hodgkin's disease in Brazil has been reported in Recife 22 , Salvador 2 3 and São Paulo 9 .…”
Section: Palavras-chaves: Vírus Epstein-barr Mononucleose Infecciosamentioning
confidence: 99%